Restricting new forests to conservation lands severely constrains carbon and biodiversity gains in New Zealand. (January 2015) - Carswell, Fiona E.; Mason, Norman W.H.; Overton, Jacob McC.; Price, Robbie; Burrows, Lawrence E.; Allen, Robert B.
Highlights: Afforestation was simulated on conservation and all New Zealand private lands. New privately-owned forests gain more C and biodiversity than on conservation land. Biodiversity suffered more trade-off when carbon was prioritised than vice versa. Prioritisation for mean C and biodiversity still improved biodiversity overall. Abstract: Increased afforestation of non-productive land could deliver win–win solutions for greenhouse gas mitigation through carbon sequestration and biodiversity gains, referred to here as increased 'ecological integrity'. We examined the potential trade-offs when selecting non-forested lands in New Zealand for natural forest regeneration to maximise gains in either, or both, carbon and biodiversity. We also examine the effect on potential gains and trade-offs of excluding non-conservation lands from spatial planning for conservation. The most significant per-hectare gains, for both carbon and biodiversity, were those occurring on non-conservation lands because conservation lands are mainly restricted to low-productivity environments where indigenous vegetation is already well represented. By contrast, productive environments, such as alluvial plains, where almost no indigenous vegetation remains, are primarily on non-conservation lands. These lands will need to be included in any reforestation strategy or else the most degraded ecosystems will not be restored. We found that biodiversity suffers a greater trade-off when carbon gain is prioritised than carbon does when biodiversity is prioritised. Trade-offs between carbon and biodiversity were higher on non-conservation lands but decreased with increasing area regenerated. Our study shows that natural regeneration will provide substantial increases in carbon and biodiversity on non-conservation lands compared with conservation lands. This emphasised the need for improved incentives to private land owners if carbon and biodiversity gain from afforestation is to be maximised.